1995
DOI: 10.1111/j.1439-0523.1995.tb00790.x
|View full text |Cite
|
Sign up to set email alerts
|

Purity control of F1‐hybrid tomato cultivars by RAPD markers

Abstract: Randomly amplified polymorphic DNA (RAPD) markers were applied in purity control of hybrid seed production of tomato [Lycopersicon esculentum Mill.). DNA from three commercial F,-hybrid cultivars and their parental lines was subjected to RAPD screening with 50 primers. Two of four primers which detected polymorphism between the parents tested, generated paternal-specific RAPDs, enabling a clear distinction to be made between hybrids and their maternal parents. In addition, combination of the polymorphic DNA p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…Similar to present study, use of SSR markers for genetic purity testing has been demonstrated in rice (Nandakumar et al, 2004); in maize (Wang et al, 2002) and in sunfl ower (Pallavi et al, 2011) and overall data remained comparable with fi eld grow out test. Similar to SSR marker applied in present study with minimum sample size; number of workers with other plants have applied different sample size of seeds for RAPD primers for example: 400 seeds in chicory (Bellamy et al, 1998), 120 in canola (Marshall et al, 1994), 40 in tomato (Rom et al, 1995), 30 in Chinese cabbage (Meng et al, 1998) and 10-20 in pepper (Ballester and Vicente, 1998) to assess the genetic purity of the hybrid seeds.…”
Section: Resultsmentioning
confidence: 99%
“…Similar to present study, use of SSR markers for genetic purity testing has been demonstrated in rice (Nandakumar et al, 2004); in maize (Wang et al, 2002) and in sunfl ower (Pallavi et al, 2011) and overall data remained comparable with fi eld grow out test. Similar to SSR marker applied in present study with minimum sample size; number of workers with other plants have applied different sample size of seeds for RAPD primers for example: 400 seeds in chicory (Bellamy et al, 1998), 120 in canola (Marshall et al, 1994), 40 in tomato (Rom et al, 1995), 30 in Chinese cabbage (Meng et al, 1998) and 10-20 in pepper (Ballester and Vicente, 1998) to assess the genetic purity of the hybrid seeds.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, it is best measured using selectively neutral genetic markers such as random amplified polymorphic DNA (RAPD; Williams et al, 1990). The RAPD markers do not depend on the environmental conditions and are present in all plant parts (Rom et al, 1995). They can identify a great number of polymorphisms that allow the distinction among accessions and the identification of possible duplicates (Bastianel et al, 1998).…”
Section: Climate Region Stage and Rainfall Of Cakile Maritima Populatmentioning
confidence: 99%
“…These traits can be identified in gene pool conserved in situ and in ex situ germplasm collections through different techniques such as molecular markers. The molecular markers, such as RAPD (Randomly Amplified Polymorphic DNA), do not Fabiane Rabelo da Costa 1* , Telma Nair Santana Pereira 1 Genetic diversity among Capsicum accessions using RAPD markers depend on the environmental conditions and are present in all plant parts (Rom et al 1995). They can identify a great number of polymorphisms that allow the distinction among accessions and the identification of possible duplicates (Bastianel et al 1998).…”
Section: Introductionmentioning
confidence: 99%